Nasal symptoms among residents in moldy housing - Ruoppi, Pirjo I; Husman, Tuula M; Reiman, Marjut H; Nuutinen, Juhani; Hyvärinen, Anne M; Nevalainen, Aino I (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'The aim of this study was to determine whether mold allergy mediated through immunoglobulin E (IgE) was responsible for the chronic nasal symptoms experienced by residents of moldy dwellings. A secondary aim was to investigate whether nasal mucosal findings were a possible reflection of other pathological mechanisms of chronic rhinitis. ' ' METHODS ': 'Sixteen adults living in moldy housing and complaining of chronic rhinitis were compared with sixteen healthy referents without any known mold exposure. All the buildings were surveyed for visible signs of moisture and mold. Microbial measurements were performed in the damp buildings with mold problems and in half of the reference buildings. The clinical study consisted of an otorhinolaryngological examination, nasal cytology, and skin prick tests. In the study cases, nasal provocation tests with fungi cultured from the homes and nasal mucosal biopsy were performed. ' ' RESULTS ': 'In the housing with signs of moisture and mold, the concentrations of microorganisms were elevated, but were within the normal range of those of the reference buildings. The only positive skin reaction for molds was detected in one referent. No reactions were elicited in the nasal provocation tests with molds. Squamous metaplasia were detected in four biopsies and three cytograms of the cases but not in the nasal smears of the referents. ' ' CONCLUSIONS ': 'In this material, the respiratory symptoms reported by occupants of moldy residences were not caused by mold allergy but were apparently related to nonspecific inflammation following irritation.
Keywords: adult; allergy; dampness; fungi; indoor air; moisture damage; mold; moldy housing; nasal symptom; resident; rhinitis; upper respiratory symptom